Nitrogen Fertilization of Soybean Affects Root Growth and Nodulation on Two Soil Types in Mississippi. Issue 2 (19th January 2018) - McCoy, Justin M.; Kaur, Gurpreet; Golden, Bobby R.; Orlowski, John M.; Cook, Donald R.; Bond, Jason A.; Cox, Michael S.
ABSTRACT: Greenhouse studies were conducted to evaluate the influence of nitrogen (N) sources [urea + ​N-( n -butyl) thiophosphoric triamide, NBPT (urease inhibitor) and polymer-coated urea (PCU)] and rates on soybean root characteristics, nodule formation, and biomass production on two soil types (silt loam and clay) commonly cropped to soybean in Mississippi. About 15% less belowground biomass was produced in clay soil than in silt loam soil directly corresponding to all other root parameters including root length, root area, root diameter, and nodule number. Pooled across N rates, N additions resulted in 19% and 52% decrease in belowground biomass and number of nodules, respectively, across soils compared to soybean receiving no N. The N rate was the most critical factor as it influenced all root growth parameters. Number of nodules were 24% greater with PCU than urea + NBPT. Nitrogen additions and clay soil negatively impacted soybean root growth, nodulation, and belowground biomass production. Abbreviations : Polymer-coated urea, PCU; N-( n -butyl) thiophosphoric triamide, NBPT